Presence of Fusarium spp. complex in diseased trees of Gmelina arborea Roxb (melina) in Ecuador. (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The area planted with Gmelina arborea (melina) in Ecuador hasincreased in the last decade, currently this forest species is affectedby the disease "vascular wilt and stem rot", which is killing thousandsof trees in the country. Ceratocystis fimbriata is listed as the causativeagent of the disease, However, the complex symptoms and thefrequent isolation of Fusarium spp. from diseased trees, make ussuspect that this phytopathogen is involved in the pathogenesis ofmelina. Koch's Postulates were applied at the greenhouse level, andfor the effect, 5 treatments based on the inoculation of 17 G. arboreaplants of 4-month-old per treatment were plated. T1 = Fusarium sp.1,T2 = Fusarium sp.2, T3 = Fusarium sp.3, T4 = Fusarium sp.4, and T5 =agar-agar (control). A complete randomized design (CRD) was usedand the plants were evaluated 155 days after inoculation. Thetreatments Fusarium sp.1 and Fusarium sp.2 caused the largestapparent volumes of necrosis (2.31 cm3 and 2.43 cm3), and generatedmild symptoms of disease, however they did not die, so these resultscannot be considered conclusive yet. It is necessary to continueinvestigating the role of Fusarium spp. in the pathogenesis of melina.